2022
DOI: 10.1021/acsami.2c09649
|View full text |Cite
|
Sign up to set email alerts
|

Ethynyl and Furyl Functionalized Porphyrin Complexes as New Organic Cathodes Enabling High Power Density and Long-Term Cycling Stability

Abstract: Organic cathode materials have recently attracted abundant attention due to their flexible structural tunability and recyclability. However, the low intrinsic electrical conductivity and high solubility in electrolytes of organic electrode materials have significantly limited their practical application. Herein, we present [5,15-bis(ethynyl)-10,20-difurylporphinato] copper(II) (Cu-DEOP) as a new cathode for rechargeable organic lithium batteries (ROLBs). The combination of both ethynyl and furyl groups of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(57 reference statements)
0
5
1
Order By: Relevance
“…A comparative CV measurement (Figure S20) suggests that an additional redox peak, which occurs at 2.7 V in the anodic scan and reverses at 2.5 V in the cathodic scan, could be attributed to the copper atom in the porphyrin core structure. Previous research also reported on partial Cu(II) to Cu(I) redox reaction in Cu−porphyrins [25a,29,41a,42] . However, in this study, we observe the reaction to be more reversible and complete than previous studies have suggested.…”
Section: Resultscontrasting
confidence: 92%
“…A comparative CV measurement (Figure S20) suggests that an additional redox peak, which occurs at 2.7 V in the anodic scan and reverses at 2.5 V in the cathodic scan, could be attributed to the copper atom in the porphyrin core structure. Previous research also reported on partial Cu(II) to Cu(I) redox reaction in Cu−porphyrins [25a,29,41a,42] . However, in this study, we observe the reaction to be more reversible and complete than previous studies have suggested.…”
Section: Resultscontrasting
confidence: 92%
“…[18][19][20][21][22][23][24] Moreover, the formation of p-conjugated aromatic compounds by introducing heteroatoms (S, O, and N) with a lone pair of electrons to organic materials might lead to multiple redox centers. [25][26][27] Compared with other organic electrode materials, the porphyrin compounds have high stability due to their rigid and extended frameworks. Cui and coworkers synthesized tetrakis(4-carboxyphenyl)porphyrin as an anode, where superior electrochemical performance (548.4 mA h g À1 and 43000 cycles) was achieved due to the large p-conjugated system.…”
mentioning
confidence: 99%
“…During the first anodic sweep (Figure 2a), two anodic peaks appeared that might be ascribed to the oxidation of CuDEFcP into cationic species [CuDEFcP] 4+ and the peak located at 3.51 V is mostly associated with the oxidation of ferrocene units into ferrocenium [16d,21] . The observed irreversible process is a common feature for this class of compounds and will be discussed further later [14a,15a,22] . In the reverse scan, four cathodic peaks were observed.…”
Section: Resultsmentioning
confidence: 90%